PRESIDENTIAL THRESHOLD DALAM PELAKSANAAN PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN PASCAPUTUSAN MAHKAMAH KONSTITUSI NOMOR 14/PUU-XI/2013 - , MOHAMMAD GHOZA F ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The ruling of the Constitutional Court No. 14/PUU-XI/2013 change system of organizing elections in Indonesia, through this ruling election held simultaneously. Holding of elections is simultaneously gave rise to implications of the implementation mechanism for the elections of the President and Vice President, particularly in terms of implementation of presidential threshold. Depart from the Constitutional Court Verdict Nmor 14/PUU-XI/2013, in this study the author raises two issues, which is what the runway judge in arguing the ruling No. 14/PUU-XI/2013? What about the implications of Ruling No. 14/PUU-XI/2013 against the provisions of the presidential threshold, still relevant peyelenggaraan threshold applied in the presidential elections simultaneously? To answer the question of the formulation of the problem the authors use research methods in library studies with approach case studies focusing on the viewpoint of juridical and conceptual point of view, so that the results of the discussion, data analysis, and the conclusions drawn up by the author can match the title of the research and outline of issues raised. Based on the results of the research, then get the basic conclusion that the judge's argument on the decision of the Constitutional Court No. 14/PUU-XI/2013 that the concurrent elections is the mechanism that mandated by the Constitution, the Constitutional Court delineates basing on original intent of article 22E paragraph (2) that the framers of the amendment to the CONSTITUTION of 1945 was the holding of the elections conducted simultaneously. Simultaneous elections were proceeding in formyl (seen in terms of the sustainability of the system) gives the implication of presidential threshold which indicates that its application be irrelevant due to the concurrent elections did not allow for a flying a pair of would-be President and Vice President are based on the number of seats to political parties in the HOUSE of REPRESENTATIVES/the number of valid national votes tally of political parties in the legislative elections.